The effect of e-counseling to reduce stress on nurses in special wards COVID-19 - Widiyanto, Juli; Yarnita, Yeni; Santoso, Santoso; Huda, Mega Hasanul (MEDISAINS, 2021)
Background: Data on the incidence of COVID-19 is reported to be increasing day by day. It impacts the health of health workers both physically and mentally; several previous studies have found that counseling can help reduce anxiety. Other studies have also proven that remembrance therapy can reduce stress levels, but the effectiveness of e-counseling has not yet been tested.Objectives: This study was to determine the effect of e-counseling to reduce stress on nurses in special wards COVID-19.Method: The research design used was a quasi-experimental design with a total sample of 58 people, 29 intervention samples, and 29 control samples. Sampling using non-probability sampling and data collection using a questionnaire which was analyzed with the Independent Sample T-Test.Result: After e-counseling therapy was carried out, the stress level of nurses could decrease significantly from 7.448 to 6.311. There were significant differences in stress levels in the intervention and control groups (69.59±6.311 vs. 49.83±8.824; p<0.05).Conclusion:  E-Counseling has a very significant effect on reducing the stress level of nurses in special wards COVID-19.